2008
DOI: 10.1111/j.1440-1843.2008.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of multifocal micronodular pneumocyte hyperplasia associated with tuberous sclerosis in Japan

Abstract: (80%) were women and the mean age was 37 years. Three patients had a family history of TSC. The radiological findings were small multiple nodular shadows with ground-glass opacity randomly distributed in the bilateral whole-lung fields in most patients. Differentiation from multiple atypical adenomatous hyperplasia or metastatic lung cancer was necessary in most patients. In 11 patients, the diagnostic method used to identify pulmonary lesions of MMPH with TSC was VAT. Among the complications of MMPH with TSC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…These lesions stain with cytokeratin and surfactant proteins A and B, but not with HMB-45, alpha smooth muscle actin, or hormonal receptors. 55 MMPH does not have known prognostic or physiologic consequences, although there have been at least two reports of respiratory failure associated with MMPH. 55,56 The precise prevalence of MMPH in patients with TSC is not known, but may be as high as 40–58%.…”
Section: Clinical Diagnostic Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…These lesions stain with cytokeratin and surfactant proteins A and B, but not with HMB-45, alpha smooth muscle actin, or hormonal receptors. 55 MMPH does not have known prognostic or physiologic consequences, although there have been at least two reports of respiratory failure associated with MMPH. 55,56 The precise prevalence of MMPH in patients with TSC is not known, but may be as high as 40–58%.…”
Section: Clinical Diagnostic Criteriamentioning
confidence: 99%
“…55 MMPH does not have known prognostic or physiologic consequences, although there have been at least two reports of respiratory failure associated with MMPH. 55,56 The precise prevalence of MMPH in patients with TSC is not known, but may be as high as 40–58%. 57,58 There is no gender restriction and MMPH may occur in the presence or absence of LAM in patients with TSC.…”
Section: Clinical Diagnostic Criteriamentioning
confidence: 99%
“…Previous reports described only 2 patients who may have died from respiratory failure, possibly due to MMPH deterioration [15, 16]. Generally, the prognoses in most previously reported cases of MMPH seemed fair [4, 5]. In our case series, all 9 patients, even the 19-year-old patient, had not deteriorated at follow-up when clinical findings, radiographic findings, pulmonary function test results, and serum biomarkers were assessed.…”
Section: Discussionmentioning
confidence: 56%
“…Histological examination typically reveals multicentric, well-demarcated, nodular type II pneumocystic growth [1, 2]. In contrast with lymphangioleiomyomatosis (LAM), which is a more common lung manifestation in patients with TSC [3], MMPH is less progressive [4, 5]. However, because of its rarity, no previous study has described the detailed clinical course of the disease, such as changes in radiographic findings and pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…Typical radiological features of MMPH are multiple tiny nodules that are diffusely and randomly scattered throughout the lung [3, 4]. Kobashi et al noted that computed tomography (CT) identified ground-glass opacity (GGO) in all of the 15 patients with MMPH [5]. On the other hand, Muzykewicz et al described that 67% of TSC patients with multiple nodules had both solid and ground-glass nodules.…”
Section: Introductionmentioning
confidence: 99%